Vancomycin Therapeutic Drug Monitoring (TDM) and Its Association with Clinical Outcomes: A Retrospective Cohort - Juhaina Salim Al-Maqbali; Zahra Al Shukri; Nawf Al Sabahi; Intisar AL-Riyami; Abdullah M. Al Alawi (Elsevier, 2022)
Background: Therapeutic drug monitoring (TDM) has proven effectiveness in maintaining efficacy and reducing toxicities associated with vancomycin. A trough level of (15-20 mg/L) for MRSA serious infections is recommended. Therapeutic failure is of concern due to suboptimal routine vancomycin utilization in clinical practice. This study aims to identify factors of vancomycin TDM practice potentially associated with vancomycin-induced nephrotoxicity and therapeutic failure measured by the need to restart vancomycin therapy within 28-days and all-cause mortality in a tertiary hospital in Oman. Methods: A single-center retrospective cohort was conducted in a tertiary care hospital that included all adult patients aged ≥ 18 years treated with IV vancomycin for> 72 h. Results: Vancomycin therapeutic level was not achieved in 16.8% of the patients, and 47.5% had high levels (>20 mg/L). Vancomycin-induced nephrotoxicity occurred in 31.7% of the patients, it was restarted within 28-days in 18.8% of the patient, and 25.2% of the patients died during the same hospitalization. Univariate analysis showed old age (p < 0.01), higher baseline creatinine reading (p = 0.03), high vancomycin level (p = 0.03), and vancomycin-induced nephrotoxicity (p < 0.01) were associated with increased all-cause mortality. Multivariate analysis identified overweight and vancomycin-induced nephrotoxicity were independent factors associated with increased all-cause mortality (OR:1.04; p = 0.043; 95% CI 1.00-1.08) and (OR:1.96; p = 0.049; 95% CI 1.00-21.61) respectively. Conclusion: Failure to achieve the recommended therapeutic vancomycin level (15-20 mg/L) is common in clinical practice and associated with poor health outcomes; hence, appropriate TDM practice is an essential exercise to improve efficacy, prevent failure and reduce serious toxicities associated with vancomycin therapy.